Avaliação transversal da qualidade de vida de cuidadores de crianças e adolescentes com câncer por meio de um instrumento genérico 36 item short form health survey questionnaire (SF-36) - Cunha, Cristiane Martins (2007)
Cancer in children and adolescents can compromise the health and well being of both patients and their family members. Over time, exposure to pain, suffering and the likelihood of death become sources of emotional, family and social instability, particularly for the parents who tend to be directly responsible for their children s care. The objective of the present study were to assess health related quality of life (HRQL) of caregivers of children and adolescents with cancer using a generic instrument 36-item Short Form Health Survey Questionnaire (SF-36) and to verify the psychometric properties of this instrument. The SF-36 was completed by 73 caregivers (mean age =38.4 years; SD=8.5) of children and adolescents with cancer (mean age =10.4 years; SD=3.7). The scores achieved for SF-36 domains were compared to scores of caregivers who had no chronic diseases (mean age=37.2 years; SD=9.1) who cared for healthy children and adolescents (control group), according to cancer type (central nervous system, leukemias and solid tumors), treatment phase and presence of chronic disease or mood disorder in caregivers. The psychometric properties (data quality, reliability and validity) of the SF-36 were verified. The reliability (Chronbach s alpha coefficient> 0.5) and the discriminant validity proved acceptable for all domains of the questionnaire. The scores achieved by caregivers of children and adolescents with cancer were significantly lower than scores of the control group (p<0.05) on both physical and mental components. Mood disorder in caregivers correlated with physical and mental function compromise as well as presence of chronic disease for functional capacity only (p<0.05). There was no significant difference amongst scores achieved according to cancer type or treatment phase. The Brazilian version of the SF-36 is valid for assessing health related quality of life (HRQL) of caregivers of children and adolescents with cancer. These caregivers present a significant negative impact on both physical and psychosocial function.